STRATEGI PENINGKATAN DAN PENJUALAN PUPUK UREA BERDASARKAN TINGKAT KEPUASAN PELANGGAN DENGAN PENDEKATAN SERVQUAL DAN QFD - Wafiyatul Hidayah; Erni Puspanantasari Putri (JUSTI (Jurnal Sistem dan Teknik Industri), 2021)
Petrokimia Gresik is a subsidiary of PT. Pupuk Indonesia which produces fertilizer in support of the Government's Program to Increase Agricultural Production and National Food Security. In one of the Work Units, namely the Administration and Sales Department, there is one Fertilizer that rarely has income that does not meet the Company's RKAP Quantum Target, namely Urea fertilizer as evidenced by the Pre-Research results, Quantum Data Realization and Quantum Target RKAP Urea Fertilizer in 2021. In the research This analysis is carried out by analyzing customer perceptions and expectations using the Servqual Method to Measure Service Quality of the Urea Fertilizer Sales and Administration Department. Measurement results in finding the gap between Customer Perceptions and expectations from Servqual will be corrected with QFD. Then do the preparation of strategies that are applied to the Company. The results of Servqual show that all dimensions have a "Unsatisfied" Satisfaction Level, which means that the customer assesses that the service provided has not met the expectations of the customer. Next, an analysis is carried out using QFD which shows that the average of all attributes needs to be improved. Indicators that require Top Priority are those related to the Competence of the Urea PIC. So the recommendation from the AVP of Urea Fertilizer is to conduct a Procurement Evaluation of the Performance of the urea PIC at the Administration and Sales Department at PT. Petrokimia Gresik.